Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
[tex](2x^4)^{-4}=2^{-4}\cdot (x^4)^{-4}=\dfrac{1}{2^4}\cdot \dfrac{1}{(x^{4})^4}=\dfrac{1}{16}\cdot \dfrac{1}{x^{16}}=\dfrac{1}{16x^{16}}[/tex]
[tex]{ \left( { \left( 2x \right) }^{ 4 } \right) }^{ -4 }\\ \\ =\frac { 1 }{ { \left( { \left( 2x \right) }^{ 4 } \right) }^{ 4 } }[/tex]
[tex]\\ \\ =\frac { 1 }{ { \left( 2x \right) }^{ 16 } } \\ \\ =\frac { 1 }{ { 2 }^{ 16 }{ x }^{ 16 } } \\ \\ =\frac { 1 }{ 65536{ x }^{ 16 } } [/tex]
[tex]\\ \\ =\frac { 1 }{ { \left( 2x \right) }^{ 16 } } \\ \\ =\frac { 1 }{ { 2 }^{ 16 }{ x }^{ 16 } } \\ \\ =\frac { 1 }{ 65536{ x }^{ 16 } } [/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.